Positive plate and lithium ion battery
By setting an active material layer and a lithium supplement layer on the positive electrode sheet and adding a functional coating to the ceramic coating of the separator, the problem of increasing battery thickness expansion rate and gas production in the existing positive electrode sheet under a high voltage system is solved, and the problem of increasing battery thickness expansion rate and gas production in the existing positive electrode sheet is realized. Improved battery capacity retention rate.
Patent Information
- Application Number
- CN202411360524.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-14
AI Technical Summary
The existing positive electrode sheet has problems with the expansion rate of the battery thickness and the increase in gas production under high voltage systems, which affects the capacity retention rate of the battery.
A positive electrode sheet is designed, including a current collector, an active material layer and a lithium supplement layer. By controlling the tap density ratio of the active substance and the lithium supplement material, it ensures that the tap density of the lithium supplement material is less than or equal to the tap density of the active substance. , and a functional coating is added to the ceramic coating of the diaphragm, containing a light stabilizer to absorb reactive oxygen or oxygen.
It effectively reduces the thickness expansion rate and gas production of the battery, improves the capacity retention rate of the battery, and reduces the compaction density loss caused by lithium supplement material.
Smart Images

Figure CN119447160A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of secondary batteries, and in particular to a positive electrode sheet and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have been widely used in consumer electronics, electric vehicles and other fields due to their high energy density, long cycle life and environmental friendliness. With the continuous development of lithium-ion battery technology and the growing market demand, consumers have put forward higher and higher requirements on the mileage and service life of lithium-ion batteries.
[0003] The existing positive electrode lithium replenishment technology has the advantages of a wide range of material selection, good compatibility, low cost and high safety. However, during the production process, due to the large difference in the tap density of the lithium replenisher and the tap density of the positive electrode material, the compaction density of the electrode sheet is reduced after mixing. In addition, in high-voltage systems, active oxygen or oxygen is released during the delithiation process of the lithium replenisher and the positive electrode material, causing the battery to produce gas and affect performance.
[0004] Therefore, it is necessary to develop a positive electrode sheet and a lithium-ion battery that can reduce the battery thickness expansion rate and gas production while improving the battery capacity retention rate under a high voltage system. Summary of the invention
[0005] The purpose of the present invention is to provide a positive electrode sheet to address the deficiencies of the prior art, which can reduce the battery thickness expansion rate and gas production while improving the battery capacity retention rate under a high voltage system.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A positive electrode sheet comprises a current collector, an active material layer and a lithium replenishing layer, wherein the active material layer is coated on at least one surface of the current collector, and the lithium replenishing layer is coated on the outer surface of the active material layer;
[0008] The active material layer contains active material, the lithium replenishing layer contains lithium replenishing material, the tap density of the active material is ρ1, the tap density of the lithium replenishing material is ρ2, wherein ρ1 and ρ2 satisfy the relationship: 0.1≤ρ2 / ρ1≤1.
[0009] Preferably, the tap density ρ1 of the active material is 1.0 g / cm2-10.0 g / cm2, and the tap density ρ2 of the lithium supplement material is 1.0 g / cm2-4.0 g / cm2.
[0010] Preferably, the mass proportion of the lithium replenishing material in the lithium replenishing layer is 0.01-6%.
[0011] Preferably, the Dv50 of the lithium supplementing material is 2-10 μm, and the Dv50 of the active substance is 5-30 μm.
[0012] Preferably, the compaction density of the positive electrode sheet is 2-4.5 g / cm 3 .
[0013] In addition, the present invention also provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator spaced between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the above-mentioned positive electrode sheet.
[0014] Preferably, the diaphragm includes a base film, a ceramic coating and a functional coating; the ceramic coating is coated on at least one surface of the base film, and the functional coating is coated on the outer surface of the ceramic coating facing the positive electrode sheet.
[0015] Preferably, the thickness of the functional coating is 0.5-4 μm.
[0016] Preferably, the functional coating comprises a binder and a light stabilizer, and the mass proportion of the light stabilizer in the material coating is 0.1-10%.
[0017] Preferably, the light stabilizer is one or more of UV-3346, TH-944, Tinuvin 770, Tinuvin 144 and Sanduvor VSU.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1) The present invention can reduce the influence of the material morphology change of the lithium supplement material after delithiation on the electrode structure by arranging an active material layer and a lithium supplement layer on the positive electrode sheet, and at the same time control ρ1 and ρ2 to satisfy the relationship: 0.1≤ρ2 / ρ1≤1. Since the tap density of the lithium supplement material is smaller than that of the positive electrode active material, the compaction density loss caused by the lithium supplement material can be reduced, thereby improving the capacity retention rate of the battery.
[0020] 2) The present invention provides a functional coating on the ceramic coating of the diaphragm, wherein the functional coating contains a light stabilizer, which can absorb the damage to the electrolyte solvent caused by the release of active oxygen or oxygen when lithium-supplementing materials and active substances in the positive electrode sheet are delithiated under a high voltage system. The amino functional group on the light stabilizer can react with oxygen free radicals to block the damage of oxygen free radicals to the electrolyte solvent, thereby reducing the gas production of the battery and reducing the expansion rate of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the structure of a positive electrode sheet according to an embodiment of the present invention.
[0022] Figure 2 Schematic diagram of the structure of a diaphragm according to an embodiment of the present invention.
[0023] Among them, 1-current collector; 2-active material layer; 3-lithium replenishing layer; 4-base film; 5-ceramic coating; 6-functional coating. DETAILED DESCRIPTION
[0024] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0025] According to a first aspect of the present application, the present application aims to provide a positive electrode sheet, comprising a current collector 1, an active material layer 2 and a lithium replenishing layer 3, wherein the active material layer 2 is coated on at least one surface of the current collector 1, and the lithium replenishing layer 3 is coated on the outer surface of the active material layer 2;
[0026] The active material layer 2 contains active material, and the lithium replenishing layer 3 contains lithium replenishing material. The tap density of the active material is ρ1, and the tap density of the lithium replenishing material is ρ2, wherein ρ1 and ρ2 satisfy the relationship: 0.1≤ρ2 / ρ1≤1.
[0027] Among them, an active material layer is coated on at least one surface of the current collector, and a lithium supplement layer is coated on the outer surface of the active material layer, which can reduce the influence of the material morphology change after delithiation of the lithium supplement material on the electrode structure, and at the same time control ρ1 and ρ2 to satisfy the relationship: 0.1≤ρ2 / ρ1≤1. Since the tap density of the lithium supplement material is smaller than that of the positive electrode active material, the compaction density loss caused by the lithium supplement material can be reduced, thereby improving the capacity retention rate of the battery.
[0028] In some embodiments, the tap density ρ1 of the active material is 1.0 g / cm-10.0 g / cm, for example, it can be 1.0 g / cm, 2.0 g / cm, 3.0 g / cm, 4.0 g / cm, 5.0 g / cm, 6.0 g / cm, 7.0 g / cm, 8.0 g / cm, 9.0 g / cm, 10.0 g / cm; the tap density ρ2 of the lithium supplement material is 1.0 g / cm-4.0 g / cm, for example, it can be 1.0 g / cm, 2.0 g / cm, 3.0 g / cm, 4.0 g / cm.
[0029] In some embodiments, the active material is one or more of lithium cobalt oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
[0030] In some embodiments, the active substance accounts for 80-99% by weight.
[0031] In some embodiments, the lithium supplement material is one or more of Li2NiO2, Li2CuO2, Li2MoO2, Li5FeO4, Li6CoO4, Li6MnO4, Li5VO4
[0032] In some embodiments, the mass proportion of the lithium supplement material in the lithium supplement layer is 0.01-6%, for example, it can be 0.01%, 0.1%, 1%, 2%, 3%, 4%, 5%, 6%. When the mass proportion of the lithium supplement material is too small, the positive electrode capacity will be low and the energy density will be low; when the mass proportion of the lithium supplement material is too large, the compaction density of the pole piece will be lost, and lithium deposition will occur during the battery cycle.
[0033] In some embodiments, the Dv50 of the lithium-supplementing material is 2-10μm, for example, it can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm. When the particle size of the lithium-supplementing material is too large, lithium ions will escape, thereby affecting the capacity performance of the battery; the Dv50 of the active material is 5-30μm, for example, it can be 5μm, 10μm, 15μm, 20μm, 25μm, 30μm.
[0034] In some embodiments, the compaction density of the positive electrode sheet is 2-4.5 g / cm 3 , for example, it can be 2g / cm 3 , 2.5g / cm 3 , 3g / cm 3 , 3.5g / cm 3 , 4g / cm 3 , 4.5g / cm 3 .
[0035] According to a second aspect of the present application, the present application provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet mentioned above.
[0036] In some embodiments, the separator includes a base film 4, a ceramic coating 5 and a functional coating 6; the ceramic coating 5 is coated on at least one surface of the base film 4, and the functional coating 6 is coated on the outer surface of the ceramic coating 5 facing the positive electrode sheet.
[0037] In some embodiments, the thickness of the functional coating 6 is 0.5-4 μm, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 4 μm. When the thickness of the functional coating is too small, the oxygen absorption effect is not obvious and the battery expansion rate increases; when the thickness of the functional coating is too large, the lithium ion migration path increases, the battery polarization increases, and the battery cycle performance and energy density are reduced.
[0038] In some embodiments, the functional coating 6 includes a binder and a light stabilizer, and the mass proportion of the light stabilizer in the material coating is 0.1-10%, for example, it can be 0.1%, 1%, 2%, 4%, 6%, 8%, or 10%.
[0039] In some embodiments, the light stabilizer is one or more of UV-3346, TH-944, Tinuvin 770, Tinuvin 144, and Sanduvor VSU.
[0040] The current collector can be any material suitable for use as a positive electrode current collector for lithium-ion batteries in the art. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to aluminum foil.
[0041] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer may include but is not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; silicon-based materials can be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; tin-based materials can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be various materials in the art that are suitable for use as a negative electrode current collector for lithium-ion batteries. For example, the negative electrode current collector may include but is not limited to metal foil, and more specifically may include but is not limited to copper foil.
[0042] The lithium-ion battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.
[0043] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0044] Example 1
[0045] (1) Preparation of positive electrode
[0046] 1. Add active material (lithium cobalt oxide), conductive agent (SP), binder (PVDF), and dispersant (PVP) in a mass ratio of 92wt%: 2wt%: 4.5wt%: 1.5wt% into a homogenization tank to prepare and homogenize the active material slurry, wherein the solid content is 74% and the viscosity is controlled at 5000mPa·s;
[0047] 2. The active material (lithium cobalt oxide), lithium supplement material (lithium ferrite), conductive agent (SP), binder (PVDF), and dispersant (PVP) are added into a homogenization tank in a mass ratio of 91wt%:1%:2wt%:4.5wt%:1.5wt% to prepare a lithium supplement slurry having a solid content of 74% and a viscosity of 5000mPa·s.
[0048] 3. Apply the active material slurry in step 1 on both sides of the current collector, apply the lithium supplement slurry in step 2 on the outer surface of the active material layer, and roll-press to form a positive electrode sheet.
[0049] Among them, the Dv50 of lithium cobalt oxide is 15μm and the tap density is 5.1g / cm 3 ; The Dv50 of lithium ferrite is 6μm and the tap density is 2.7g / cm 3 The compaction density of the positive electrode is 4.2g / cm 3 .
[0050] (2) Preparation of negative electrode
[0051] Graphite, conductive agent carbon nanotubes, binder styrene butadiene rubber, and thickener sodium carboxymethyl cellulose were stirred and mixed in deionized water at a mass ratio of 97.2:1.2:0.8:0.8. After being mixed evenly, the negative electrode slurry was coated on Cu foil, baked, rolled, and cut into strips to obtain a negative electrode sheet.
[0052] (3) Preparation of diaphragm
[0053] The binder PVDF and the photocatalyst (UV-3346) were dissolved in a polypyrrolidone (NMP) solvent at a mass ratio of 99%:1% and mixed evenly to obtain a mixed slurry with a solid content of 25%. The mixed slurry was coated on the surface of the ceramic coating with a coating thickness of 1 μm.
[0054] (4) Preparation of electrolyte
[0055] An organic solution is obtained by mixing the following components and mass ratios: ethylene carbonate (EC): propyl propionate (PP): vinylene carbonate (VC): diethyl carbonate (DEC): propylene carbonate (PC) = 22:25:3:28:22; lithium salt LiPF6 is added to the organic solution, and the mass ratio of the added mass to the organic solution is 9.5:90.5; after mixing evenly, an electrolyte is obtained.
[0056] (5) Preparation of batteries
[0057] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order and wound to obtain an electrode assembly; the electrode assembly is placed in a packaging shell, an electrolyte is injected into the packaging shell and the packaging is performed to finally obtain a lithium-ion battery.
[0058] The preparation methods of Examples 2-7 and Comparative Examples 1-6 are the same as the preparation method of Example 1, except for the composition and parameters of the positive electrode sheet and the separator, as shown in Table 1-2 below.
[0059] Table 1
[0060]
[0061]
[0062] Table 2
[0063]
[0064] Test method:
[0065] (1) Gas production test: Fill a fixed container with water and record the initial value V1. Charge the lithium-ion secondary battery to 4.53V at 80°C at a constant current of 1.0C and a current of 0.05C. Place the battery cell with the air bag in the container and record the value V2. The gas volume V = V2-V1.
[0066] (2) Capacity retention test: At 25°C, the lithium-ion secondary battery was charged to 4.53V at a constant current of 1.0C and a current of 0.05C, left to stand for 5 minutes, and then discharged to 3V at a constant current of 0.7C. This is a charge and discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. The lithium-ion secondary battery was subjected to 1000 cycles of charge and discharge tests according to the above method, and the discharge capacity of each cycle was recorded.
[0067] Cycle capacity retention rate (%) = discharge capacity of the nth cycle / discharge capacity of the first cycle (n is the number of cycles)
[0068] (3) Thickness expansion rate test: At 25°C, record the initial thickness T0 of the battery, charge the lithium-ion secondary battery to 4.53V at a constant current of 1.0C and 0.05C, let it stand for 5 minutes, and then discharge it to 3V at a constant current of 0.7C. This is a charge and discharge cycle. The lithium-ion secondary battery is cycled according to the above method and the thickness Tn is tested every 100 cycles.
[0069] Thickness expansion ratio (%) = (Tn-T0) / T0.
[0070] The test results are shown in Table 3.
[0071] Table 3
[0072]
[0073]
[0074] From the data comparison of Examples 1-11 and Comparative Examples 1-6 in Table 3, it can be seen that the positive electrode sheet and lithium-ion battery provided by the present application can reduce the compaction density loss caused by the lithium supplement material and improve the capacity retention rate of the battery; and the amine functional group on the light stabilizer in the functional coating in the diaphragm can react with oxygen free radicals to block the damage of oxygen free radicals to the electrolyte solvent, reduce the gas production of the battery, and reduce the expansion rate of the battery.
[0075] From the data comparison of Examples 1-3 and Comparative Example 3, it can be seen that when other parameters do not change, as the mass proportion of lithium supplement material increases, the gas production of the battery will increase, the capacity retention rate will decrease, and the thickness expansion rate will increase. This is due to excessive lithium supplementation and lithium deposition in the battery. When the mass proportion value is too large, lithium metal will be deposited on the negative electrode side of the battery, the capacity will decay, and the thickness will increase.
[0076] From the data comparison of Examples 1, 4-7 and Comparative Examples 1, 5, it can be seen that when the material coating thickness is too large, the lithium ion migration path will increase, the battery polarization will increase, resulting in a decrease in capacity retention and an increase in thickness.
[0077] From the comparison of the data of Example 1 and Comparative Example 6, it can be seen that when the compaction density of the positive electrode sheet is too large, it will cause the material particles to break and the cycle to drop.
[0078] From the data comparison of Example 1 and Comparative Example 4, it can be seen that when the tap density of the active material is less than the tap density of the lithium supplement material, the compaction density of the electrode will be low, affecting the energy density of the battery.
[0079] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A positive electrode sheet, characterized in that: It comprises a current collector, an active material layer and a lithium replenishing layer, wherein the active material layer is coated on at least one surface of the current collector, and the lithium replenishing layer is coated on the outer surface of the active material layer; The active material layer contains active material, the lithium replenishing layer contains lithium replenishing material, the tap density of the active material is ρ1, the tap density of the lithium replenishing material is ρ2, wherein ρ1 and ρ2 satisfy the relationship: 0.1≤ρ2 / ρ1≤1.
2. A positive electrode sheet according to claim 1, characterized in that: The tap density ρ1 of the active material is 1.0 g / cm2-10.0 g / cm2, and the tap density ρ2 of the lithium supplement material is 1.0 g / cm2-4.0 g / cm2.
3. A positive electrode sheet according to claim 1, characterized in that: The mass proportion of the lithium replenishing material in the lithium replenishing layer is 0.01-6%.
4. The positive electrode sheet according to claim 1, characterized in that: The Dv50 of the lithium supplement material is 2-10 μm, and the Dv50 of the active material is 5-30 μm.
5. The positive electrode sheet according to claim 1, characterized in that: The compaction density of the positive electrode sheet is 2-4.5 g / cm 3 .
6. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet according to any one of claims 1 to 5.
7. A lithium ion battery according to claim 6, characterized in that: The diaphragm includes a base film, a ceramic coating and a functional coating; The ceramic coating is coated on at least one surface of the base film, and the functional coating is coated on the outer surface of the ceramic coating facing the positive electrode sheet.
8. A lithium ion battery according to claim 7, characterized in that: The thickness of the functional coating is 0.5-4 μm.
9. A lithium ion battery according to claim 7, characterized in that: The functional coating comprises a binder and a light stabilizer, and the mass proportion of the light stabilizer in the material coating is 0.1-10%.
10. A lithium ion battery according to claim 9, characterized in that: The light stabilizer is one or more of UV-3346, TH-944, Tinuvin 770, Tinuvin 144 and Sanduvor VSU.
Citation Information
Patent Citations
Lithium ion battery diaphragm and lithium ion battery equipped with same
CN109585749A
Lithium supplement additive and preparation method and application thereof
CN115312767A
Pole piece preparation method, positive plate, electrochemical device and electronic equipment
CN118588881A
Cited By
Long-circulation aluminum shell lithium ion battery and preparation method thereof
CN121688157A